STRATEGI PEMASARAN JASA PENDIDIKAN - Siti Ana Asma Usania (Universitas Nurul Jadid, 2021)
This study aims to determine the marketing strategies and models of educational services at SMP Al Shadrina Muaradua. This research uses a qualitative approach with a case study type. The results showed that the data obtained in the form of exposure of the seven marketing mixes and the steps of promotional activities resulted from the data from the acquisition of students for three years experienced an increase. From the results of marketing activities, it was found that the most effective marketing activities were advertising, cooperation between public relations and all school members (such as market day activities and other school activities), personal interest, and also the use of good and appropriate media and promotional tools. The marketing strategy for education services at SMP Al Shadrina Muaradua has been implemented well, but documentation needs to be done to make it better.